The black orb - Kim, Ewhan (Mira, 2025)
"One evening in downtown Seoul, Jeong-su is smoking a cigarette outside when he sees something impossible: a huge black orb appears out of nowhere and sucks his neighbour inside. The orb soon begins consuming other people and no one knows how to stop it... Impervious to bullets and tanks, the orb splits and multiplies, chasing the hapless residents of Seoul out into the country and sparking a global crisis with widespread violence and looting. Jeong-su must rely upon his wits as he makes the arduous journey in search of his elderly parents. But the strangest phases of this ever-expanding disaster are yet to come and Jeong-su will be forced to question everything he's taken for granted. A piercinglydark, surreal satire on mass panic, disaster response and modern masculinity."--